2015
DOI: 10.1002/anie.201508854
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Symmetry of Multipoint Hydrogen Bonding on Chelate Cooperativity in Supramolecular Macrocyclization Processes

Abstract: Esta es la versión de autor del artículo publicado en: This is an author produced version of a paper published in: Copyright: © 2016 Wiley VCH VerlagEl acceso a la versión del editor puede requerir la suscripción del recurso Access to the published version may require subscription The Role of Multipoint Hydrogen-bond Symmetry on Chelate Cooperativity in Supramolecular MacrocyclizationsCarlos Montoro-García, [a] Jorge Camacho-García, [a] Ana M. López-Pérez, [a] María J. Mayoral, [a] Nerea Bilbao, [a] and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 30 publications
2
45
0
Order By: Relevance
“…We previously demonstrated that GC1 cyclic tetramers ( c GC1 4 ) are formed quantitatively in solvents of moderate polarity due to the strong chelate effects attained . More recent work in our group has focused on evaluating the dependence of the length of the phenylene‐ethynylene spacer that connects the two bases ( n in Figure b) on chelate cooperativity . Different monomers were prepared in which n varied from 1 to 5.…”
Section: Introductionmentioning
confidence: 99%
“…We previously demonstrated that GC1 cyclic tetramers ( c GC1 4 ) are formed quantitatively in solvents of moderate polarity due to the strong chelate effects attained . More recent work in our group has focused on evaluating the dependence of the length of the phenylene‐ethynylene spacer that connects the two bases ( n in Figure b) on chelate cooperativity . Different monomers were prepared in which n varied from 1 to 5.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen bonds are arguably the most prominent of noncovalent interactions, as the very foundations of life as we know it depend crucially on H-bonding. 1 From a synthetic point of view, a wealth of host–guest systems, 2 supramolecular polymers, 3 and molecular machines 4 based on H-bonding has been described. 5 Unsurprisingly, measuring and understanding H-bonds has been the subject of intensive research efforts, and it still busies the scientific community.…”
Section: Introductionmentioning
confidence: 99%
“…[b] Determined as EM = K T / K ref 4 using the data calculated from the NMR dilution in [D 6 ]DMF (Figure S2B), NMR dilution in [D 8 ]THF (Figure S2 A), NMR competition experiments with C in CDCl 3 (Figure S3 B), respectively. [c] EM values ranging between 2.2×10 2 –3.6×10 2 m (DMF), 1.8×10 2 –7.3×10 2 m (THF), and 8.1×10 2 –9.1×10 2 m (CHCl 3 ) were previously determined by us for GC1 …”
Section: Figurementioning
confidence: 82%
“…We recently reported an example of a dinucleoside monomer ( GC1 ; Figure b) based on a π‐conjugated p ‐diethynylbenzene unit substituted with complementary nucleobases at the edges: guanine (G) and cytosine (C), which have bulky lipophilic ribose groups to afford solubility and prevent stacking interactions. This rigid and linear structure, together with the 90° angle provided by Watson–Crick pairing, resulted in the formation of unstrained square‐shaped H‐bonded cyclic tetramers ( c GC1 4 ), which displayed remarkable thermodynamic and kinetic stabilities ascribed to the large EM values attained (10 2 –10 3 m ) ,. Further investigations allowed us to conclude that such record chelate cooperativities stem from: 1) a rigid predisposed monomer geometry, and 2) an unsymmetric (i.e.…”
Section: Figurementioning
confidence: 93%
See 1 more Smart Citation